Efficient post-treatment-free polymer solar cells from indacenodithiophene and fluorinated quinoxaline-based conjugated polymers. (July 2018) - Gao, Yueyue; An, Che; Wang, Zhen; Sun, Yanming; Wei, Zhixiang; Guo, Fengyun; Yang, Yulin; Zhao, Liancheng; Zhang, Yong
Abstract: Two novel narrow bandgap copolymers PIDTFPQ and PIDTFTQ based on bulky indacenodithiophene (IDT) and mono-fluorophenanthrenequinoxaline (FPQ) or mono-fluorodithienobenzoquinoxaline (FTQ), which possess a large fused phenanthrene or benzodithiophene ring on top of pyrazine unit, are designed and synthesized. The optical properties, electrochemical properties, π-π packing behavior, charge carrier transport, morphology and photovoltaic properties of two copolymers were thoroughly investigated via a series of techniques. Owing to the smaller volume of dithienobenzoquinoxaline, PIDTFTQ shows more planar structure. Furthermore, PIDTFTQ presents slightly red-shifted onset absorption and denser π-π stacking. Besides, PIDTFTQ:PC71 BM blend film displays higher hole and electron mobilities of 1.46 × 10 −4 cm 2 V −1 s −1 and 2.64 × 10 −4 cm 2 V −1 s −1 than those of PIDTFPQ/PC71 BM blend film. More excitingly, without using any additives or any thermal/solvent annealing, the polymer solar cells based on PIDTFTQ/PC71 BM and PIDTFPQ/PC71 BM obtained higher Voc of 0.92 V and 0.93 V and promising PCE of 5.54% and 5.00%, respectively. The results show that PIDTFTQ or PIDTFPQ possess a great potential for large area roll-to-roll manufacturing or printing technology for PSCs. Graphical abstract: Highlights: Polymers PIDTFPQ and PIDTFTQ based on indacenodithiophene and fluorinated quinoxalines have been synthesized. The optical and electrochemical properties as well as the polymer packing behaviors of both polymers were investigated. A promising power conversion efficiency of up to 5.54% was obtained. The photovoltaic performances were achieved without any solvent additives or any thermal/solvent annealing treatments.